2013
DOI: 10.1002/ppul.22967
|View full text |Cite
|
Sign up to set email alerts
|

The cystic fibrosis gender gap: Potential roles of estrogen

Abstract: Cystic fibrosis (CF) is a complex, multi-system, autosomal recessive disease predominantly affecting Caucasians that leads to vigorous airway inflammation and chronic respiratory infection, commonly with Pseudomonas aeruginosa. A variety of factors significantly modify the progression and severity of CF lung disease and the timing of the resulting mortality. We summarize here data indicating that there is in CF a female disadvantage in survival and morbidity, called the "CF gender gap". Although controversy ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 64 publications
0
59
2
Order By: Relevance
“…Indeed, in CF there is a female disadvantage in terms of survival and morbidity, called the “CF gender gap” [28], which might be due to the female sex hormone estrogen. Nevertheless, it is unclear from the literature whether women with CF are in greater pain than men with CF.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in CF there is a female disadvantage in terms of survival and morbidity, called the “CF gender gap” [28], which might be due to the female sex hormone estrogen. Nevertheless, it is unclear from the literature whether women with CF are in greater pain than men with CF.…”
Section: Discussionmentioning
confidence: 99%
“…[1, 2] The exact reason for this gender gap remains unclear; and various factors such as sex hormones, differences in immune responses, socio-economic factors, and variations in airway diameter have all been implicated. [1][2][3][4] Lung transplantation (LT) is a widely accepted modality of treatment for select CF patients with progressive disease. In the United States, donors and recipients are matched based on ABO compatibility, size, virtual crossmatch, and need for single versus bilateral lungs.…”
Section: Introductionmentioning
confidence: 99%
“…Given the lack of apparent differences in patient characteristics between male and female CF patients in our population which may account for the observed female predominance in airway inflammation, there is some room for speculation. It has been shown that oestrogen has a complex immunomodulatory effect on inflammation and mucoid P. aeruginosa density [19]. Human CF patients whose lungs are actively infected with P. aeruginosa have elevated sputum levels of IL-23 and IL-17 which decrease dramatically following antibiotic treatment [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Sex hormones also modulate autoimmunity. Autoimmune diseases are a class of illnesses associated with increased Th17 activity and showing distinct gender-based differences in prevalence [19]. The gender-based difference in inflammation in our CF population may be the result of overstimulation of Th17 activity by oestrogens similar to what is seen in autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%